Agama Dan Interaksi Sosial: Potret Harmoni Beragama Di Wiyono Kabupaten Pesawaran - Suhandi, Suhandi (Universitas Islam Negeri Raden Intan Lampung, 2018)
In its capacity as social beings, humans tend to relate and interact with their environment. As for social interaction, it is always preceded by social contact and communication. This contact is then followed by processes that are associative or disassociative or opposition. The associative process begins with cooperation then continues with accommodation, assimilation, and acculturation. This research focuses on efforts to portray the harmonization of religious communities in the Wiyoni area of Pesawaran District. From the results of the study it can be concluded that: Social interactions that occur are more directed at dynamic interactions where the occurrence of mutually beneficial two-way interactions that result in associative interactions that are mutually reinforcing. So that this leads to the realization of harmonization in inter-religious life. While the factors that support the occurrence of interaction are mutual respect between one religion to another (Islam and Christianity), support from religious leaders, and ethnically in the village. Wiyono is mostly Javanese who culturally promote culture of mutual respect for each other.